Agronomic evaluation of chickpea (Cicer arietinum L.) genotypes in contrasting agro-ecological regions of Limpopo and Mpumalanga Provinces - Shilenge, Siphiwe Kim (My University, 2020)
Chickpea (Cicer arietinum L.) is an important grain legume in the world, ranking second after soybean (Glycine max L.). It accounts for a substantial proportion of human dietary nitrogen intake and plays a crucial role in food security in developing countries. Chickpea can grow in areas with low rainfall and poor soils, and thus may be an important food security crop for smallholder resource-poor farmers in the semi-arid tropics such as the dry environments of the Limpopo and Mpumalanga Provinces of South Africa. Preliminary studies showed the huge potential of chickpea production in these environments. However, no suitable genotypes have been identified and recommended for different agro-ecological zones of Limpopo and Mpumalanga Provinces. Therefore, the objective of this study was to evaluate the performance, and hence, identify the genotypes that are adapted/suitable to the contrasting agro-ecological conditions of Limpopo and Mpumalanga Provinces for production. Field experiments were conducted in the winter cropping seasons of 2016 and 2017 at Thohoyandou (University of Venda experimental station), Syferkuil (University of Limpopo experimental station) and Nelspruit (University of Mpumalanga experimental station). Ten desi chickpea genotypes were sown in a completely randomized block design replicated three times on 10 May 2016 and 10 April 2017 (Thohoyandou), 13 May 2016 and 11 April 2017 (Syferkuil) and 03 May 2016 and 24 May 2017 (Nelspruit). Plant growth characteristics were assessed by determining plant height, crop phenology, number of primary and secondary branches, and canopy cover. Yield and yield components were assessed at harvest after physiological maturity. Carbon dioxide exchange rates (CER) was determined at different growth stages using the InfraRed Gas Analyzer (IRGA). Chlorophyll content (CC) and intercepted radiation were determined weekly using the chlorophyll content meter (CCM-200 PLUS, Opti-Science, Tyngsboro, Massachusetts), and the AccuPAR, LP-80 ceptometer (Deacon Devices Ltd., Pullman, USA), respectively. Genotypes did not vary in CC at Thohoyandou in all seasons, but CC increased with stages of growth. Genotypes varied in the proportion of intercepted radiation (IR) at all measurement dates in Thohoyandou during the 2016 and 2017 growing seasons. The proportion of IR increased with growth stage, reached a peak and declined with plant age. Genotype affected photosynthesis and intercellular CO2 concentration (Ci) but did not have any significant effect on stomatal conductance (gs), transpiration (T) and Leaf Vapour Pressure Deficit (VPDL) during the 2016 season in Thohoyandou. In contrast, genotype did not affect photosynthesis, Ci, gs, T and VPDL in the 2017 season in Thohoyandou. There was no variation among genotypes on number of primary and secondary branches in Thohoyandou in both seasons. Genotypes showed no variation in plant height in the 2016 season in Thohoyandou agro-ecological condition. However, genotypes showed significant variation in plant height at 14, 70 and 84 days after emergence (DAE) in the 2017 cropping season. Moreover, genotypes showed significant variations in days to 50% flowering in Thohoyandou during the 2016 season, but showed no variations in days to 50% emergence and 75% physiological maturity. Genotypes showed no variations in days to 50% emergence, 50% flowering, 50% podding and 75% physiological maturity in the 2017 season in all locations. Genotypes showed significant variation in grain yield in Syferkuil agro-ecological condition, but showed no significant variations on all the other studied traits, while genotypes varied in 100 seed weight (SW) in Thohoyandou, but did not show any variations on the other studied traits during the 2016 season. Moreover, genotypes did not vary for all studied traits in Nelspruit during the 2016 season. The 2016 genotype and environment (G X E) interaction results showed no significant variations. However, results showed G X E interactions during the 2017 growing season suggesting that genotypes responded to environmental variation in a different way. Syferkuil had the greatest grain yield (2811 kg ha-1 and 3122 kg ha-1) in both the 2016 and 2017 growing seasons respectively, as compared to Thohoyandou and Nelspruit. These preliminary findings show that the studied genotypes responded differently in contrasting agro-ecological regions of Limpopo and Mpumalanga Provinces and that Syferkuil might be the best environment for chickpea production in this region due to its cooler temperatures. Of the genotypes evaluated the most promising genotypes are ICCV8101, ICCV3203 and ICCV4110 in these regions in terms of grain yield.
MSCAGR (Plant Production)
Department of Plant Production
Keywords: Agro-ecological; Environment; UCTD; Genotypes; Semi-arid; Yield components; 633.37096827; Chickpea -- South Africa -- Mpumalanga; Cicer -- South Africa -- Mpumalanga